Chaos synchronisation in high-order circuits and time-delay systems using observer - G. Grassi; S. Mascolo (Electronics Letters, 1999)
An observer-based technique is described for the synchronisation of complex chaotic dynamics, generated by systems with several positive Lyapunov exponents. The tool is used to synchronise, via a scalar signal, a recent example of an eighth-order circuit and a cell equation in a delayed cellular neural network.